2021
DOI: 10.3390/cancers13215413
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid-Appended Hydroxypropyl-β-Cyclodextrin Exhibits Potent Antitumor Activity in Chronic Myeloid Leukemia Cells via Autophagic Cell Death

Abstract: 2-Hydroxypropyl-β-cyclodextrin (HP-β-CyD) is widely used as an enabling excipient in pharmaceutical formulations. We previously demonstrated that HP-β-CyD disrupted cholesterol homeostasis, and inhibited the proliferation of leukemia cells by inducing apoptosis and cell-cycle arrest. Recently developed drug delivery systems using folic acid (FA) and folic acid receptors (FR) are currently being used in cancer treatment. To confer tumor cell-selectivity to HP-β-CyD, we synthesized folate-appended HP-β-CyD (FA-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…Interestingly, the analogue of cucurbiturils (molecules forming complexes according to the guest-host type)–cyclodextrin and calixarenes have not cytotoxic activity against the K562 tumor line as also cucurbituril. However, complex formation or modification of the nanosubstance’s structure increases their antitumor activity in regard chronic myeloid leukemia [ 46 , 47 ]. Increased antitumor activity was associated with apoptosis of these cells, but it is not clear whether this is due to the generation of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the analogue of cucurbiturils (molecules forming complexes according to the guest-host type)–cyclodextrin and calixarenes have not cytotoxic activity against the K562 tumor line as also cucurbituril. However, complex formation or modification of the nanosubstance’s structure increases their antitumor activity in regard chronic myeloid leukemia [ 46 , 47 ]. Increased antitumor activity was associated with apoptosis of these cells, but it is not clear whether this is due to the generation of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of hydroxypropyl cyclodextrin with a folate group as described for the materials above could be performed to provide a material with the capability to cause autophagic cell death in chronic myeloid leukemia cells, especially when combined with imatinib, an ABL tyrosine kinase inhibitor [89]. In mouse models, this combined therapy had a much stronger inhibitory effect on cancer progression than either component separately.…”
Section: Medical Applicationsmentioning
confidence: 99%
“…The IC 50 values of Ara-C for HL-60, THP1 and SKM1 cells were 0.495 µM, 7.19 µM and 0.6 µM, respectively, and those of Venetoclax were 50.3 nM, 441.8 nM and 1.1 µM, respectively. The combination index (CI) and Fa values for each dilution were calculated using CalcuSyn software (version 1.1.1), as reported previously (Figures S8-S10) [22,33]. Dose-effect and CI-Fa plots illustrating the effect of the combinations of FA-HP-β-CyD and Ara-C or Venetoclax are presented in Figure 6.…”
Section: Fa-hp-β-cyd Acts Synergistically To Enhance the Effects Of A...mentioning
confidence: 99%
“…Previously, we showed that HP-β-CyD exerts antitumor activity against BCR-ABL-positive cells, but its lack of tumor cell selectivity raised concerns about systemic cytotoxicity [21]. Therefore, we synthesized folate-appended HP-β-CyD (FA-HPβ-CyD) [22] to increase tumor cell selectivity (folate receptors (FRs) are highly expressed by tumor cells) [23,24], and showed that FA-HP-β-CyD was not toxic to FR-negative cells; however, it induced both apoptosis and autophagic cell death in chronic myeloid leukemia (CML) cells [22].…”
Section: Introductionmentioning
confidence: 99%